Influence of Leadership Style and Organizational Culture Job Satisfaction Against Performance at PTPN 3 Nusantara Medan - Mutiara Gom-Gom Roito Nadapdap; Melinda Siregar; Sugianto Lumbantoruan; Adika Fajar Putra; Nella Selvina Br Tarigan (East Asian Journal of Multidisciplinary Research, 2023)
The purpose of the study was to examine and analyze the influence of Leadership style, organizational culture, and job satisfaction on Performance at PTPN 3 Nusantara Medan. This research approach is quantitative and descriptive. The nature of this study is explanatory-descriptive research. This data analysis model uses multiple regression analyses. The results of the study as well as the conclusion of the research are that leadership style partially has a significant effect on Performance at PTPN 3 Nusantara Medan. Organizational culture partially has a significant effect on Performance at PTPN 3 Nusantara Medan. Partial job satisfaction has a significant effect on performance at PTPN 3 Nusantara Medan. Leadership style, organizational culture, and job satisfaction simultaneously affect Performance at PTPN 3 Nusantara Medan.